Anticipating Cybersecurity on Artificial Intelligence - Thandy Simanjuntak (International Journal of Information System and Innovative Technology, 2023)
As artificial intelligence (AI) continues to revolutionize various sectors, the intersection of AI and cybersecurity has emerged as a critical frontier. This paper delves into the realm of "Anticipating Cybersecurity on Artificial Intelligence," exploring the challenges, opportunities, and strategies inherent in safeguarding AI systems against an evolving landscape of cyber threats. With AI playing an increasingly pivotal role in decision-making, automation, and data analysis, the security of AI systems becomes paramount to ensuring the integrity and trustworthiness of their outcomes. This paper investigates various dimensions of anticipating cybersecurity concerns in AI, including identifying potential vulnerabilities, developing proactive defense mechanisms, and fostering collaboration between AI and cybersecurity experts. Through an in-depth analysis of recent case studies and trends, we highlight the importance of pre-emptive measures to thwart adversarial attacks, data poisoning, and model manipulations. Moreover, we explore the role of explainable AI in enhancing cybersecurity transparency and the potential for leveraging AI techniques to enhance intrusion detection and threat mitigation. By delving into these interconnected aspects, this paper not only underscores the urgency of addressing cybersecurity within AI but also emphasizes the necessity of anticipating future threats to ensure the continued success and trustworthiness of AI technologies. In sum, this study contributes to the discourse surrounding AI cybersecurity, shedding light on strategies to anticipate and counteract threats, and fostering a holistic approach to secure the AI-driven future.